Analisis Tindakan Scorched-Earth Policy (Taktik Bumi Hangus) oleh Junta Militer Myanmar Terhadap Suku Rohingya di Rakhine Menurut Hukum Humaniter Internasional (BELLI AC PACIS, 2019)
This article analyzes the use of scorched earth policy, and an indication of crimes against humanity which are commited by Military Junta of Myanmar against Rohingya tribes based on International Humanitarian Law. This article uses normative research methods, namely research based on legal materials which its focus is conducted by studying primary and secondary legal materials. Based on the study, the author concludes that Military Junta of Myanmar brutally and sadistically commited scorched earth tactic in order to sweep away Rohingya ethnics from its territory. Though Military Junta did commit the scorch earth tactis, there is an indication that Military Junta of Myanmar also commited crime against humanity along with the scorched earth, such as deportation or forced eviction, rape and forced pregnancy, and systematic massive killing. These acts explicitly violate Additional Protocol I of the 1977 Geneva Convention and the Rome Statute of 1998.